2009
DOI: 10.1017/s096272860000052x
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion on UK milk marketing and dairy cow welfare

Abstract: Interview questionnaires were administered to the general public in central Scotland and northern England during summer 2007 to investigate consumer awareness of UK dairy production methods, welfare issues and recognition of ‘quality assurance’ product logos. Fifty percent of respondents gave UK dairy animal welfare a positive rating. Recognition of individual quality assurance logos was poor and 75% of respondents stated that they did not intentionally seek to buy products with any of the logos. Respondents’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, public understanding of animal welfare and farming practices is mediated by a range of socio-demographic factors (see Clark et al 2016;Cornish et al 2016;Evans & Miele 2019). When members of the public are asked to self-assess their level of knowledge, many report that they know little about production methods (Frewer et al 2005;Boogaard et al 2006;Ellis et al 2009;Cummins et al 2015;Eurobarometer 442 2016;Cardoso et al 2017); to some extent this may even reflect willful ignorance (McKendree et al 2014;Bell et al 2017). However, when people are directly tested on their knowledge, a more complex picture often emerges; for example, in a previous study we found that public participants often already knew about lack of pasture access and other housing practices for dairy cattle (Ventura et al 2016a).…”
Section: Low Knowledgementioning
confidence: 99%
“…However, public understanding of animal welfare and farming practices is mediated by a range of socio-demographic factors (see Clark et al 2016;Cornish et al 2016;Evans & Miele 2019). When members of the public are asked to self-assess their level of knowledge, many report that they know little about production methods (Frewer et al 2005;Boogaard et al 2006;Ellis et al 2009;Cummins et al 2015;Eurobarometer 442 2016;Cardoso et al 2017); to some extent this may even reflect willful ignorance (McKendree et al 2014;Bell et al 2017). However, when people are directly tested on their knowledge, a more complex picture often emerges; for example, in a previous study we found that public participants often already knew about lack of pasture access and other housing practices for dairy cattle (Ventura et al 2016a).…”
Section: Low Knowledgementioning
confidence: 99%
“…Additionally, it has been discovered that consumer ideals of sustainability, health, and naturalness overlap when it comes to organic products [10]. Even though there is little evidence to support this claim, consumers tend to believe that organic dairy products are naturally healthier, more natural, better for the environment, and better for animal welfare than their conventional counterparts [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Public concern for the quality of life of farm animals has received much attention in recent years (Ellis et al, 2009;Ahmed et al, 2020). In the dairy sector specifically, lack of cow-calf contact (CCC) after birth is one of the more contentious practices, which is generally controversial for the public (Busch et al, 2017;Placzek et al, 2021;Sirovica et al, 2022).…”
Section: Introductionmentioning
confidence: 99%